RNA-binding protein RBM3 intrinsically suppresses lung innate lymphoid cell activation and inflammation partially through CysLT1R - Badrani, Jana H.; Strohm, Allyssa N.; Lacasa, Lee; Civello, Blake; Cavagnero, Kellen; Haung, Yung-An; Amadeo, Michael; Naji, Luay H.; Lund, Sean J.; Leng, Anthea; Kim, Hyojoung; Baum, Rachel E.; et al. (Nature communications, 2022)
Innate lymphoid cells (ILC) promote lung inflammation in asthma through cytokine production. RNA-binding proteins (RBPs) are critical post-transcriptional regulators, although less is known about RBPs in ILC biology. Here, we demonstrate that RNA-binding motif 3 (RBM3) is highly expressed in lung ILCs and is further induced by alarmins TSLP and IL-33. Rbm3 −/− and Rbm3 −/− Rag2 −/− mice exposed to asthma-associated Alternaria allergen develop enhanced eosinophilic lung inflammation and ILC activation. IL-33 stimulation studies in vivo and in vitro show that RBM3 suppressed lung ILC responses. Further, Rbm3 −/− ILCs from bone marrow chimeric mice display increased ILC cytokine production suggesting an ILC-intrinsic suppressive function of RBM3. RNA-sequencing of Rbm3 −/− lung ILCs demonstrates increased expression of type 2/17 cytokines and cysteinyl leukotriene 1 receptor (CysLT1R). Finally, Rbm3 −/− Cyslt1r −/− mice show dependence on CysLT1R for accumulation of ST2 + IL-17 + ILCs. Thus, RBM3 intrinsically regulates lung ILCs during allergen-induced type 2 inflammation that is partially dependent on CysLT1R. The function of RNA binding proteins within innate lymphoid cells (ILC) has been partially characterised. Here the authors show that RBM3 functions to limit the type 2 immunity promoting activity of ILC2 partially through cysteinyl leukotriene 1 receptor.